Cambios en el patrón electroforético del veneno de la serpiente cascabel muda (Lachesis muta stenophrys) almacenado bajo diferentes condiciones - Gené, José A. (1985)
Liquid and lyophilized samples of Lachesis muta venom were stored at different temperatures and for different periods of time, and analyzed by polyacrylamide gel electrophoresis (PAGE) and immunoelectrophoresis. Only slight variations were evident when three pools of freeze-dried venom, that had been kept at -30°C for several months were compared with fresh venom. These results suggest that L. muta venom is not altered drastically when stored under these conditions.